Sex differential mediation effects of planning within the health behavior change process. (August 2018) - Lange, Daniela; Barz, Milena; Baldensperger, Linda; Lippke, Sonia; Knoll, Nina; Schwarzer, Ralf
Abstract: Objective: Previous research demonstrates that planning mediates the relationship between intention and health behavior change, but evidence is inconclusive, and possible sex differences within the intention-planning-behavior-chain are understudied so far. The current study, therefore, aims to disentangle this by addressing potential sex differences in the mediating role of planning in the health behavior change process. Method: Three longitudinal studies were conducted in Germany between 2009 and 2011 (Study 1: 245 women, 216 men; Study 2: 156 women, 37 men; Study 3: 82 women, 84 men). In each study, intention (predictor), planning (mediator), and sex (moderator) were assessed to predict changes in (1) fruit and vegetable intake, (2) physical activity, and (3) sun protection. A moderated mediation model was specified to test whether the conditional direct effect of intention on health behavior change and/or the conditional indirect effect of intention on health behavior change through planning was different for men and women. Results: Similar patterns of sex differential effects emerged within the intention-planning-behavior-chain across all three studies. The conditional indirect effect of intention on health behavior change through planning was meaningful for men but not for women for all three health behaviors. Thus, planning acted as a mediator between intention and health behavior change only for men. Conclusion: The study contributes to the understanding of the inconclusive evidence on the role of planning as mediator between intention and health behavior change and sheds some light of possible sex differences that qualify this mediation. The findings suggest that women and men may not similarly benefit from health behavior change modification techniques involving planning strategies. Future theoretical developments and interventions should take this into account. Highlights: There is inconclusive evidence of the mediation effect of planning. This study seeks to shed light on possible sex differences that qualify this mediation. Similar sex differential mediation effects emerged across three longitudinal studies. Planning mediated between intention and health behavior change only for men. Sex-specific interventions for health behavior changes are important.